Urgensi Pendidikan Pancasila dan Kewarganegaraan terhadap Pembentukan Karakter Peserta Didik - Ubaidillah (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2018)
Indonesia is a multi-ethnic country, race, ethnicity, language, culture and religion. This diversity often triggers disharmony among citizens. Violence committed by one group with another group in the name of ethnicity, religion, race, and so on is a concrete example of disharmony that often occurs in our society. One effort to overcome this is through the introduction of the importance of Pancasila education and citizenship to the formation of character so that it can produce good citizens, especially at elementary school level students. The way of introduction must also be adjusted to the characteristics of the child because this will affect the physical and psychological condition of the child if the way of introduction is not appropriate. The cultivation of knowledge is then continued with the application in daily life and the need for habituation as well as role models so that they can develop capabilities and shape the character and dignity of a nation.